Tinospora crispa ethanolic extract downregulates Protein Kinase genes expression and activity during Toxoplasma gondii infection: a prospective drug target for lytic cycle inhibition - Abdullahi, Sharif Alhassan; Nordin, Norshariza; Unyah, Ngah Zasmy; Basir, Rusliza; Daneji, Isa Muhammad; Nasiru, Wana Mohammed; Majid, Roslaini Abd (College of Graduate Studies, Walailak University, 2023)
Infection with Toxoplasma gondii remains widespread among humans and animals as water, soil and food continue to serve as the major carriers of the sporulated oocyst. The infection is poorly controlled due to lack of a potent vaccine against the parasite, and the current medication presents severe side effects on the host, less efficacy on the parasite and is accompanied by the potential development of resistance by the parasite. The aim of this study was to evaluate the in vitro activities of ethanolic extract of Tinospora crispa (EETC) on protein kinases involved in the lytic cycle of T. gondii infection in Vero cell line. The EETC was obtained through the maceration of dried stem powder. Vero cells infected with the RH strain of T. gondii were used to evaluate the inhibitory effect of EETC against T. gondii calcium dependent protein kinase (CDPK) genes and microneme proteins (MIC) that are essential for host cell invasion and intracellular replication of the tachyzoite. Gene expression profiling of CDPK genes was determined through quantitative real-time PCR (qPCR) after 24 h of treatment. The expression of microneme protein was determined through western blot technique. The RT-qPCR revealed downregulation of most protein kinase (PK) genes after treatment with EETC. The expression of CDPK1, PKG, CDPK3, CDPK6, CDPK7 genes that participate in the lytic cycle of T. gondii infection was downregulated. The expression of the TgMIC1 and TgMIC2 proteins were observed to have decreased in both 4 and 24 h post-infection treatment models. This study showed that EETC contains promising drug candidates effective against T. gondii that can target the protein kinase genes involved in the lytic cycle of the parasite to prevent disease progression.